Adipose-Derived Mesenchymal Stem Cells Promote M2 Macrophage Phenotype through Exosomes - June Seok Heo; Youjeong Choi; Hyun Ok Kim (Hindawi Limited, 2019)
Accumulating evidence has shown that the paracrine factors derived from mesenchymal stem cells (MSCs) are capable of regulating the immune system via interaction with various immune cells. In this study, adipose-derived MSCs (AdMSCs) and human peripheral blood monocytes (PBMCs) were isolated and cultured to examine the effects of MSC-induced macrophages (iMΦ) on inflammation and immune modulation. Indirect coculture with MSCs increased the expression of arginase-1 and mannose receptor (CD206), markers of activated M2 macrophages, in the PBMCs demonstrating that MSC-secreted factors promoted M2-MΦ polarization. Additionally, iMΦ exhibited a similar higher inhibitory effect on the growth of activated T cells compared to that in the other groups (AdMSCs only, AdMSCs plus iMΦ), implying that iMΦ can play a sufficient functional role. Interestingly, the population of FoxP3 Treg cells significantly increased when cocultured with iMΦ, suggesting that iMΦ have an immunomodulatory effect on the Treg cells through the modulation of the FoxP3 expression. Notably, iMΦ expressed high levels of immunosuppressive and anti-inflammatory cytokines, namely IL-10 and TSG-6. Furthermore, we confirmed that the AdMSC-derived exosomes modulated macrophage polarization by upregulating the expression of M2 macrophage markers. Conclusively, our results suggest that iMΦ play a significant role in regulating the immunomodulatory- and inflammatory-mediated responses. Thus, iMΦ may be used as a novel stem cell-based cell-free therapy for the treatment of immune-mediated inflammatory disorders.